(untitled) (Historia, 2021)
This review article looks at two recent books on white voices in South Africa and Zimbabwe, by Nicky Falkof and Irikidzayi Manase respectively. Together they offer insight on how different historical contexts affected white fears of belonging in the colonial and post-colonial state. For Falkof, the final death throes of apartheid caused a range of moral panics among white communities. This panic expressed itself largely in moral terms with the issues of Satanism and family murder becoming paramount. Manase’s book, however, focuses on a very different historical context. Manase investigates the outpouring of accounts written by white Zimbabweans since 2000 and the start of the fast-track land reforms. He seeks to answer questions about why so many books were produced at this time; how they portrayed the land reforms; and how they narrated questions of race, belonging and politics. Ultimately, Manase notes, the long contestation over land in Zimbabwe still dramatically affects recent and current accounts of belonging and victimhood. These publications raise some interesting questions about conducting research into whiteness in southern Africa and the different ways of undertaking such studies. While there are points of issue in both books, they utilise a range of methodologies and approaches that should stimulate further research and facilitate critical engagement on histories of whites and whiteness by a broader community of scholars.